The digital economy : - Tapscott, Don (McGraw-Hill, 1996)
A smart survival manual for companies marketing online services and products via the Internet and its World Wide Web, this entry in a crowded field is distinguished by a minimum of hype and a recognition that the global, interactive marketplace is a new business environment where old rules don't necessarily apply. As well as for its vignettes distilling the Net experiences of large, established corporations, Martin's book is particularly useful for its profiles of dozens of companies?from Silicon Valley entrepreneurs to Silicon Alley start-ups in Manhattan's Soho district?that make up what he calls the digital estate, i.e., firms that conduct business via the Internet exclusively. From these digital pioneers he gleans lessons about customizing advertising messages, encouraging interactive customer participation, making continual market feedback integral to product development and even collaborating with competitors. His "100 Rules of Business Netiquette" for e-mail and Web users set a standard for civil conduct in cyberspace. Martin, an IBM vice-president, is founding publisher of Interactive Age.